Optimal fiscal substitutes for the exchange rate in a monetary union - Christoph Kaufmann (Deutsche Bundesbank, 2016)
This paper studies Ramsey-optimal monetary and fiscal policy in a New Keynesian 2-country open economy framework, which is used to assess how far fiscal policy can substitute for the role of nominal exchange rates within a monetary union. Giving up exchange rate flexibility leads to welfare costs that depend significantly on whether the law of one price holds internationally or whether firms can engage in pricing-tomarket. Calibrated to the euro area, the welfare costs can be reduced by 86% in the former and by 69% in the latter case by using only one tax instrument per country. Fiscal devaluations can be observed as an optimal policy in a monetary union: if a nominal devaluation of the domestic currency were optimal under flexible exchange rates, optimal fiscal policy in a monetary union is an increase of the domestic relative to the foreign value added tax.
Keywords: F41; F45; E63; 330; Monetary union; Optimal monetary and fiscal policy; Exchange rate